(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Kalidasa, widely regarded as the greatest poet and dramatist of classical Sanskrit literature, occupies a unique position in Indian intellectual and cultural history. While he is often celebrated for his poetic excellence, aesthetic refinement, and mastery over language, his works also reveal profound philosophical insight. This paper examines Kalidasa not merely as a literary genius but as a philosopher-poet, with special reference to the eighth canto of the Raghuvamsa. Through a close reading of the Ajavilāpa (lament of King Aja) and the philosophical teachings delivered by the sage Vasiṣṭha, the study highlights the seamless integration of emotional depth and philosophical reflection in Kalidasa’s poetry. The analysis focuses particularly on verse 8.87, which encapsulates a significant metaphysical idea: that death is the natural state of embodied beings, while life itself is a temporary modification. This striking philosophical assertion resonates with broader Indian philosophical traditions, especially the teachings of the Bhagavad Gita, which emphasize the immortality of the soul and the transience of the body. The paper demonstrates how Kalidasa presents such ideas not through abstract discourse but through poetic expression embedded within dramatic and emotional contexts. Furthermore, the study explores Kalidasa’s ability to portray universal human experiences, such as grief, attachment, and loss, while simultaneously guiding the reader toward detachment and wisdom. The contrast between Aja’s emotional suffering and Vasiṣṭha’s philosophical detachment illustrates two levels of human existence—the empirical and the transcendental. By balancing these perspectives, Kalidasa achieves a synthesis of poetry and philosophy that is both aesthetically powerful and intellectually profound. Ultimately, this paper argues that Kalidasa’s literary works should be appreciated not only for their artistic brilliance but also for their philosophical depth, thereby justifying his recognition as a true philosopher-poet.